1970
DOI: 10.3329/bmrcb.v37i3.9120
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI in the evaluation of acoustic schwannoma and its comparison to histopathological findings

Abstract: Magnetic Resonance Imaging (MRI) has been the primary imaging modality and has revolutionized the imaging of brain tumors. MRI can display accurate multi planer imaging without interfering of adjacent structures specially for posterior fossa mass lesion. MRI is the imaging modality of choice for cerebollo-pontine (CP) angle Schwannoma. The study was performed to determine, the diagnostic accuracy of MRI in the evaluation of intracranial extra axial CP angle Schwannoma. MRI scan of brain was done on 42 consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 5 publications
6
8
0
Order By: Relevance
“…These radiological findings were well correlated with histopathological diagnosis. The results in our study were comparable to study done by Haque S et al (18) In their study the age range from 21-60 years and the mean age was 42.85 years. Highest incidence of Cerebellopontine Angle (CPA) mass (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…These radiological findings were well correlated with histopathological diagnosis. The results in our study were comparable to study done by Haque S et al (18) In their study the age range from 21-60 years and the mean age was 42.85 years. Highest incidence of Cerebellopontine Angle (CPA) mass (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Haque S et al [24] in their study of role of MRI in the evaluation of acoustic schwannoma and its comparison to histopathological findings in 2011 found that the overall sensitivity of MRI to diagnose Acoustic Schwannoma was 96 % with specificity of 88.2 %, positive predictive value of 92.31 % and accuracy of 92.86 % which is consistent with the above study.…”
Section: Discussionsupporting
confidence: 77%
“…These results are in concordance with the study conducted by Haque S et al which states that acoustic schwannomas account for nearly 70 -80% of all cerebellopontine angle lesions, followed next in frequency by meningioma and epidermoid cysts in the second and third position constituting 10 -15% and 5% of cerebellopontine angle tumours respectively. 13 The age of the patients in the present study ranged from 8 to 72 years with mean age of 51.9 +/-10.5 years which is in concordance to the study done by Mulkens and Osborn et al in which it was found that age range and mean range was 26 -80 years and 56.5 years respectively. Maximum number of cases were recorded in the age group of 51-60 years which is in accordance to previous studies stating that majority of cases are seen in people post 50 years of life.…”
Section: Discussionsupporting
confidence: 91%